Protection of Property Rights in Malaysian Civil Law: A Normative Study - Azharun Bin Azlan Azharun; La Diu Samiun Diu (Indonesian Civil Law Review, 2026)
Protection of property rights is one of the fundamental elements of civil law because it is directly related to legal certainty, social stability, and the guarantee of human rights. In Malaysia, the protection of property rights has distinctive characteristics due to the influence of a plural legal system that combines common law, Islamic law, and customary law. This condition creates its own dynamics, particularly in the regulation of land, inheritance, contracts, and the resolution of property rights disputes. This study aims to analyze the forms of property rights protection in Malaysian civil law, identify the normative foundations governing them, and assess the effectiveness of legal protection for vulnerable groups in ownership disputes. This research employs normative legal research methods using statutory, conceptual, and comparative approaches. The data used are secondary data obtained through library research, including primary legal materials such as the Federal Constitution, National Land Code 1965, Contracts Act 1950, and Specific Relief Act 1950, as well as secondary legal materials in the form of books, scientific journals, and relevant court decisions. The results of the study show that Article 13 of the Federal Constitution provides constitutional guarantees for property rights through the prohibition of arbitrary deprivation and the obligation to provide adequate compensation. The National Land Code 1965 strengthens this protection through the Torrens-based land registration system. However, the effectiveness of such protection still faces obstacles, including jurisdictional conflicts between civil courts and Syariah courts, weak recognition of indigenous peoples’ land rights, and limited legal access for women and economically disadvantaged groups. In conclusion, the protection of property rights in Malaysia should not rely solely on formal legal certainty but must also be directed toward inclusive substantive justice. Therefore, harmonization of the legal system and the strengthening of affirmative policies are necessary to ensure fairer protection for all levels of society.